2011
DOI: 10.1126/science.1211884
|View full text |Cite
|
Sign up to set email alerts
|

How a DNA Polymerase Clamp Loader Opens a Sliding Clamp

Abstract: Processive chromosomal replication relies on sliding DNA clamps, which are loaded onto DNA by pentameric clamp loader complexes belonging to the AAA+ family of ATPases. We present structures for the ATP-bound state of the clamp loader complex from bacteriophage T4, bound to an open clamp and primer-template DNA. The clamp loader traps a spiral conformation of the open clamp so that both the loader and the clamp match the helical symmetry of DNA. One structure reveals that ATP has been hydrolyzed in one subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
375
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(400 citation statements)
references
References 61 publications
22
375
3
Order By: Relevance
“…Host and viral DNA replication is contingent on rapid and processive DNA synthesis. DNA polymerase tethering to the PCNA sliding clamp permits processive replication (29). PCNA is a closed circle and requires RFC enzymatic activity to load onto and encircle DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host and viral DNA replication is contingent on rapid and processive DNA synthesis. DNA polymerase tethering to the PCNA sliding clamp permits processive replication (29). PCNA is a closed circle and requires RFC enzymatic activity to load onto and encircle DNA.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is a closed circle and requires RFC enzymatic activity to load onto and encircle DNA. RFC, an AAA+ clamp-loading ATPase, consists of five subunits (RFC1-RFC5) (26,29,30). In alternative RFC complexes, other subunits substitute for RFC1 to function in specialized pathways, such as for DNA damage (26).…”
Section: Discussionmentioning
confidence: 99%
“…A recent structural study with the T4 bacteriophage clamp loader suggested that hydrolysis of one ATP molecule causes a conformational change in the clamp loader⅐clamp complex that closes the clamp (30), and studies with the E. coli replisome suggest that hydrolysis of one ATP molecule is sufficient to form initiation complexes but hydrolysis of 3 molecules accelerates the process (31,32). Studies have shown that ATP hydrolysis is required for clamp release (24,26,33), but the question here is whether ATP hydrolysis is required for clamp closing or whether binding of the clamp loader⅐clamp complex to DNA is sufficient to promote clamp closing.…”
mentioning
confidence: 99%
“…The primase requires contact with single-stranded DNA-binding protein (SSB) (14) to remain bound to the RNA primer. Disruption of this interaction mediated by the polymerase clamp loader leads to primase displacement (14); β-clamp loading on primed DNA (15,16); and, finally, interaction of the polymerase core subunits with the β-clamp-loaded template (14,17). β-clamp loading is a complex reaction involving clamp opening and then positioning around the DNA with the use of the clamp loader (reviewed in ref.…”
mentioning
confidence: 99%